Loss of Drosophila UBE3A phenocopies Piezo dysfunction and drives hyperphagic feeding in Drosophila. - Geier, B.; Neely, L.; Coronado, E.; Reiter, L.T. (Fly, 2026)
Angelman syndrome (AS) is a rare neurogenetic disorder characterized by developmental delay, speech impairment, ataxia, epilepsy, and in some cases hyperphagic feeding behavior. AS is caused by loss of function mutations, loss of expression, or maternal allele deletion of the E3 ubiquitin ligase UBE3A. Recent work has identified a connection between UBE3A and the mechanosensitive ion channel PIEZO2, raising the possibility that UBE3A may regulate PIEZO-dependent satiety signaling. In this study, we investigated the role of the Drosophila UBE3A ortholog, Dube3a, in Piezo-associated feeding behaviors. Single-cell RNA-sequencing data revealed overlapping expression of Dube3a and Piezo within crop and enterocyte populations of the gut, identifying a relevant cellular context for this pathway to occur. We developed a novel feeding assay using GFP-expressing yeast to quantify food intake and gut distention in vivo. Dube3a loss-of-function (Dube3a[15b]) flies exhibited hyperphagia and gut distention nearly identical to Piezo knockout flies. Analysis of chromosomal deficiency lines spanning the Dube3a locus further supported a requirement for Dube3a in normal satiety signaling. Finally, biochemical analyses demonstrated that Dube3a knockdown results in decreased Piezo protein levels, consistent with an indirect regulatory relationship. Together, these findings identify Dube3a as a critical regulator of Piezo-dependent satiety pathways and suggest that dysregulation of mechanosensory signaling may contribute to hyperphagia observed in AS. Further work is needed to define the intermediate factors linking UBE3A activity to Piezo stability and function.